2004
DOI: 10.1529/biophysj.104.047738
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Adsorption to Supported, Anionic Lipid Bilayers Studied via Atomic Force Microscopy

Abstract: The adsorption of membrane-associated protein cytochrome c to anionic lipid bilayers of dioleoyl phosphatidylglycerol was studied in low ionic strength physiological buffer using atomic force microscopy. The bilayers were supported on polylysinated mica. The formation of stable, single lipid bilayers was confirmed by imaging and force spectroscopy. Upon addition of low concentrations of cytochrome c, protein molecules were not topographically visible on the lipid bilayer-buffer interface. However, the forces r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…The AFM topographic images in Figure 4 A and C are SPBs of POPE:POPC before and after the injection of cyt c into the fluid cell. In agreement with other studies (Choi and Dimitriadis, 2004), individual entities or aggregates of the protein were not observed on top of the SPB but changes in roughness and height of the bilayer. These images revealed that the protein induces a significant decrease in the height of the bilayers and a small increase in the R a of the SPB (Table 3).…”
Section: Resultssupporting
confidence: 93%
“…The AFM topographic images in Figure 4 A and C are SPBs of POPE:POPC before and after the injection of cyt c into the fluid cell. In agreement with other studies (Choi and Dimitriadis, 2004), individual entities or aggregates of the protein were not observed on top of the SPB but changes in roughness and height of the bilayer. These images revealed that the protein induces a significant decrease in the height of the bilayers and a small increase in the R a of the SPB (Table 3).…”
Section: Resultssupporting
confidence: 93%
“…We forward the readers interested in AFM studies on the interactions of small peptides, such as antimicrobial peptides, fusogenic peptides and cell-penetrating peptides with lipid bilayers to excellent reviews in the literature El Kirat et al, 2010). The reader can also find interesting AFM works on the interaction of peripheral membrane proteins such as cytochroms with supported lipid bilayers (Choi and Dimitriadis, 2004;El Kirat and Morandat, 2009). It should be stressed that the examples we will show do not represent the general behavior of membrane proteins upon phase separation in the bilayer and that the results obtained by AFM should be as much as possible compared to the results coming from other biophysical techniques.…”
Section: Chapter 2: Lipid/protein Interaction Studied By Afmmentioning
confidence: 99%
“…To date, the interaction of cyt c with model membranes was investigated with monolayer techniques (Quinn and Dawson, 1969), fluorescence spectroscopy (Gorbenko, 1999;Tuominen et al, 2002), infrared spectroscopy (Bernad et al, 2004;Bernabeu et al, 2007), nuclear magnetic resonance (Pinheiro and Watts, 1994;Kim et al, 2006), electron spin resonance (Snel and Marsh, 1994;Heimburg and Marsh, 1995), Raman spectroscopy (Vincent and Levin, 1988), circular dichroism (Cortese et al, 1998), titration calorimetry (Heimburg et al, 1999), surface plasmon resonance (SPR) (Salamon and Tollin, 1996) and atomic force microscopy (AFM) (Boussaad et al, 1998;Mueller et al, 2000;Choi and Dimitriadis, 2004;Domenech et al, 2006;Morandat and El Kirat, 2007). However, the interaction of cyt c with neutral lipid membranes is still poorly documented.…”
Section: Introductionmentioning
confidence: 99%